Case Report: Pediatric Multiple Sclerosis - Chang Segura, José Lee (2023)
Pediatric multiple sclerosis is an autoimmune, demyelinating and neurodegenerative disease of the central nervous system that affects individuals under 18 years old, the pathogenesis involves immune responses and secondary axonal damage. About 3 to 10% of MS cases occur in pediatric patients, most of them older than 15 years and mainly affect women. Pediatric MS is characterized by a relapsing-remitting course at onset. The diagnosis is based on the identification of recurrent demyelinating events in CNS separated in time and/or space. Among the differential diagnoses that must be excluded there are other demyelinating pathologies, autoimmune and systemic conditions, hereditary, infectious and metabolic diseases. Patients with pediatric multiple sclerosis take longer to reach irreversible disability states but they do it at an earlier age than those who have adult-onset multiple sclerosis. Therapies used in children are based on the results of observational studies since there are no randomized controlled trials in this population.